Where is the peri-urban? Mapping the areas ‘around, beyond and between’ - Ravetz, Joe; Sahana, Mehebub (Frontiers in Sustainable Cities, 2025)
The peri-urban, the areas ‘around, beyond and between’ the urban, may be the fastest expanding land-use around the world. Its many dimensions can include population density, economic activity, travel patterns, urban infrastructure, land cover, water basins or material flows. To explore the question ‘where is the peri-urban’, we adopt a twin-track approach. One is a conceptual ‘integrated framework’, which includes tangible parameters of land-use, relational linkages and systemic emergence. The second track is a practical ‘basic delineation’, a simple combination of population density and functional area, based on the Global Human Settlements Layer (GHSL), as developed by the project Peri-cene, through consultation with city-region partners. This delineation is here applied to a sample of 21 city-regions, covering in total 10% of the global urban population. The peri-urban land area in this sample is estimated at around 180,000 km2, with a rapid growth rate of 2.9% per annum. This basic delineation is then combined with a wider set of social, economic and governance variables, to provide a basic global typology. The same method then highlights the internal peri-urban structure and growth pattern of each city-region, to derive a typology of six main peri-urban patterns. Overall, the basic delineation provides a foundation for quantitative analysis of the global peri-urban: and also supports further investigation of more complex systems-level problems and policy pathways.